Detection of Multidrug-Resistant (MDR) Escherichia coli Isolated from Raw Milk in East Java Province, Indonesia - Ribby Ansharieta1 , Mustofa Helmi Effendi2,3, Hani Plumeriastuti4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of this study is to figure out the profile of antibiotic resistance in E. coli, sourced from raw milk,obtained from five districts in East Java Province, Indonesia. A total of 250 samples were tested usingthe Kirby-Bauer Test method. The result revealed that the highest percentage of antibiotic resistance wasTetracycline (17.05%), followed by Streptomycin (14.2%), Trimethoprim (9.66%), Chloramphenicol(7.95%) and Aztreonam (1.7%). A total of 16 E. coli isolates (9.1%) were detected as MDR, and 3 E. coliisolates (1.7%) were suspected as presumptive ESBL. Thus, threat of multidrug resistance E. coli possiblysourced from the milk.